Steady lift-force generation on a circular cylinder utilising a longitudinal vortex: Influence of geometrical parameters. Issue 212 (May 2021) - Hemsuwan, Withun; Sakamoto, Kasumi; Takahashi, Tsutomu
Abstract: A novel technique for producing a steady lift force on a circular cylinder in a uniform flow driven by the longitudinal vortex (LV) is developed. The LV forms behind the cylinder when a strip plate is located downstream in a cruciform arrangement. The upstream cylinder can stably move by itself via an aerodynamic effect of the LV-produced steady lift force. However, the effects of geometrical parameters on system performance have not been investigated. In this study, the effective parameters of the presented mechanism—the width ratio of the strip plate, W / d, and the exposed length ratio of the circular cylinder over the strip plate, l e / d —are numerically examined. An unsteady Reynolds-averaged Navier–Stokes simulation using a shear-stress-transport k–ω turbulence model is employed for this analysis. The experimental investigation in our wind tunnel laboratory is used to primarily validate the computational predictions. The distribution of the aerodynamic forces acting on the cylinder surface is continuously evaluated along the length span. Flow fields around the system are also visualised for discussion of the vortical effects. The results indicate that the proper parameters of the system needed to generate the available driving force for the moving cylinder are ( i ) a strip-plate width of 1.5 ​< ​ W/d ​< ​2.5, with W/d ​= ​2 being considered as the most suitable, and ( ii ) an optimal exposed length of the cylinder of l e ​= ​1.5 d . Highlights: Numerical results were validated with experimental data of the wind tunnel test. Flow fields were numerically visualised providing vortical structures. Aerodynamic-force distributions along the cylinder length were continuously investigated.